INOVASI MANAJEMEN OSIS DALAM MENINGKATKAN KUALITAS AKADEMIK MELALUI KEGIATAN EKSTRA KURIKULER DI SMKN 2 NGAWI: 10.56997/inisiasi.v4i2.1963 - labiibah, Kulsuum; As-zahra, Ratna; Tyas, Zuhriana Widya Rahayu Ning (Inisiasi : Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to determine the role of intra-school organizational management (OSIS) in improving academic quality through extracurricular activities at the SMKN 2 NGAWI school. This research finds that the OSIS structure greatly contributes to extracurricular activities at the school in improving the SMKN 2 NGAWI school. Management and structure of the student council in improving school quality through student skills by developing their talents through extracurricular activities which are routinely carried out once a week. The research we conducted used qualitative research methods by means of field observations and interviews. We used data collection and interview techniques through three sources, namely the OSIS supervisor, the OSIS chairman and deputy. The results of the research we conducted at SMKN 2 NGAWI regarding OSIS management innovations inimproving academic quality through extracurricular activities can draw the conclusion that the role of the OSIS is very important in the involvement of female students in developing their individual talents through extracurricular activities. It is hoped that the results of this research can make a contribution in developing extracurricular activities to improve the quality of schools at SMKN 2 NGAWI.